2021
DOI: 10.3390/e23020164
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effectiveness of Rehabilitation after Total Knee Replacement Surgery Using Sample Entropy and Classical Measures of Body Balance

Abstract: Exercises in virtual reality (VR) have recently become a popular form of rehabilitation and are reported to be more effective than a standard rehabilitation protocol alone. The aim of this study was to assess the efficacy of adjunct VR training in improving postural control in patients after total knee replacement surgery (TKR). Forty-two patients within 7–14 days of TKR were enrolled and divided into a VR group and a control group (C). The C group underwent standard postoperative rehabilitation. The VR group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…The results of this study are consistent with our previously published results that showed no significant advantage of rehabilitation with additional VR training over standard rehabilitation in terms of balance and postural control in the same group of patients [ 11 ]. Gianola et al [ 5 ] also reported no superiority of rehabilitation with VR in terms of pain relief, drug assumptions, and other functional outcomes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study are consistent with our previously published results that showed no significant advantage of rehabilitation with additional VR training over standard rehabilitation in terms of balance and postural control in the same group of patients [ 11 ]. Gianola et al [ 5 ] also reported no superiority of rehabilitation with VR in terms of pain relief, drug assumptions, and other functional outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…In the recent years, exergaming in immersive, semi-immersive, or nonimmersive virtual reality (VR) increased in popularity. Its advantages include, among others, greater patient motivation, improved (faster) effects of training, and the possibility of correcting movement strategies using feedback features of games [ 10 , 11 , 12 ]. A growing number of studies have shown the utility of training with virtual reality in restoring gait and balance in older people, especially in the backwards stepping test, crossover stepping test [ 13 ], 6-min walking test [ 14 ], and timed up-and-go test [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 . After title, abstract and full text review, 9 RCTs with 835 patients randomized to VR-based telerehabilitation vs. traditional rehabilitation following TKA were identified and included in the final review [ 1 , 4 , 5 , 8 , 10 , 13 , 24 , 26 , 35 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Virtual models lay the groundwork for comprehensive analyses of therapeutic effectiveness, offering the potential to pinpoint the most advantageous solutions for patients. Notably, these models can appraise the effect of skeletal implant geometry [ 12 ], delineate the course of patient rehabilitation, such as maneuvering with crutches [ 13 ], and assess post-surgical recuperation processes such as knee replacement [ 14 ], ligament reconstruction [ 15 , 16 ], or spinal fixation system influences [ 17 ].…”
Section: Introductionmentioning
confidence: 99%